The crystal structure of 4-(3-(triphenylphosphonio)propyl)piperazin-1-ium dibromide trihydrate, C25H37Br2N2O3P - Jia Xibei; Li Xiaomei (Zeitschrift für Kristallographie - New Crystal Structures)
C25H37Br2N2O3P, monoclinic, P21/n (no. 14), a = 9.827(5) Å, b = 14.441(8) Å, c = 10.175(6) Å, β = 103.573(16)°, V = 1403.6(13) Å3, Z = 2, Rgt (F) = 0.0530, wRref (F 2) = 0.1105, T = 296 K.